Selecting Television Programs for Language Learning: Investigating Television Programs from the Same Genre - Webb, Stuart (International Journal of English Studies, 2011)
The scripts of 288 television episodes were analysed to determine the extent to which vocabulary reoccurs in television programs from the same subgenres and unrelated television programs from different genres. Episodes from two programs from each of the following three subgenres of the American drama genre: medical, spy/action, and criminal forensic investigation were compared with different sets of random episodes. The results showed that although there were an equivalent number of running words in each set of episodes, the episodes from programs within the same subgenre contained fewer word families than random programs. The findings also showed that low frequency word families (4000-14,000 levels) reoccur more often in programs within the same subgenre. Together the results indicate that watching programs within the same subgenre may be an effective approach to language learning with television because it reduces the lexical demands of viewing and increases the potential for vocabulary learning.